2009
DOI: 10.2478/v10045-009-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR and Agar Plating Method to Predict Fusarium Verticillioides and Fumonisin B1 Content in Nigerian Maize

Abstract: Eighty maize grain samples collected in Nigeria were investigated for fumonisin B 1 (FB 1 ) content and Fusarium verticillioides colonization. F. verticillioides DNA was quantified by species-specific real-time PCR and living propagules of the fungus were counted by agar-plating method. FB 1 was detected in 55 (68.7%) of the total samples (mean: 98.5 µg/kg, range: 10 to 714 µg/kg) at 10 µg/kg detection limit. The mean amount of F. verticillioides DNA determined by real-time PCR was 49.7 µg/kg (range: 10-126.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…This is the first report on the occurrence of FBs in yam flour in Nigeria. When compared to maize in Nigeria, the levels of FB 1 obtained in this work were lower than that reported by Adejumo, Hettwer, Nutz, and Karlovsky (2009) …”
Section: Discussioncontrasting
confidence: 81%
“…This is the first report on the occurrence of FBs in yam flour in Nigeria. When compared to maize in Nigeria, the levels of FB 1 obtained in this work were lower than that reported by Adejumo, Hettwer, Nutz, and Karlovsky (2009) …”
Section: Discussioncontrasting
confidence: 81%
“…Adejumo et al [ 31 ] compared PCR analysis with an agar plating method for detection of F. verticillioides in maize samples from a Nigerian market. They found that only 71% of the maize samples that were positive for F. verticillioides by agar plating were confirmed positive by species-specific PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of F . verticillioides target DNA in a sample represented fungal colonization (Adejumo, Hettwer, Nutz, & Karlovsky, 2009; Janse van Rensburg, Mclaren, Flett, & Schoeman, 2015; Ncube, Flett, Waalwijk, & Viljoen, 2011; Rose et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The reproducibility (inter-run variance) and repeatability (intra-run variance) of the qPCR was not investigated, as this was previously performed by Boutigny et al (2012) under the same laboratory conditions using the same analytical equipment. The amount of F. verticillioides target DNA in a sample represented fungal colonization (Adejumo, Hettwer, Nutz, & Karlovsky, 2009; Janse van Rensburg, Mclaren, Flett, & Schoeman, 2015;Ncube, Flett, Waalwijk, & Viljoen, 2011;Rose et al, 2016).…”
Section: Dna Extractions and Quantification Of F Verticillioides Target Dna In Maize Grainmentioning
confidence: 99%